RESPONS UMAT BERAGAMA TERHADAP PANCASILA SEBAGAI SARANA INTEGRASI BANGSA (STUDI TENTANG PANDANGAN DAN SIKAP UMAT BERAGAMA DI SURAKARTA) - ., Winarno (PKn Progresif, 2006)
purpose of this research is to know and describe the response of Indonesian society based on religion classification against Pancasila as instrument of nation integration. The response of religious people enclosed vision and their attitude to the valves which is implied in Pancasila, the relationship between religion with Pancasila and the function of five principle as instrument for  nation integration. The purpose this research also to know the relationship between religion and Pancasila and then the influence of it for nation integration. This research approximation used  the descriptive qualitative approach with the background of religious people at Surakarta including Hindu, Budha, Islam, Khatolic and Christian. The population of this research were the pious who can give the information of data research. The technique  of sampling applied was non random sampling by purposive sampling. Beside if completed with snowball sampling to get key informan exactly.  The technique of  collecting data used in-dept interview as major technique completed with lesson of literature as a back up.To analysis of data the interactive model of analysis was used. The result of analysis showed in naration in descriptive  qualitative.This research conclude that there was many kind of response from the religious people againts  Pancasila. Their vision againts Pancasila was under influence by the judgement of their believe and knowledge about history of Pancasila. They  acknowledge Pancasila as their own thought parallel with their believe in their religion. Religious people accepted Pancasila as instrument  of nation integration because of the history that proved part of Pancasila as a meeting point between the people before independence. Acknowledgement of  this history was hopefully could be formed as long as they still want the progression of nation-state Indonesia. Pancasila was accepted as the accord agreement from society to be a state living norm.